Evaluasi Kebijakan Pembangunan Rumah Tidak Layak Huni dalam Upaya Percepatan Penanggulangan Kemiskinan di Kota Surabaya - Nia Eka Safitri; Anggraeny Puspaningtyas; Eddy Wahyudi (Public Administration Dept, Faculty of Social and Political Science, 2025)
The uninhabitable housing program (RUTILAHU) in Surabaya City is one of the programs that aims to overcome poverty for low-income people who have slums and are still below the standard value of habitable housing. The government has made several efforts through programs that can help the poor, with the aim that the program can help improve the standard of living and health of the poor. In this study, using the Bridgman & Devis (2000) policy evaluation theory which has several indicators including Input, Process, Output, Outcome. The research method uses a qualitative method by describing a situation that actually occurs in the field. Data collection techniques can be taken from accurate interview results so that it can be seen to what extent the uninhabitable housing program has been running in the last three years in Surabaya City. The author's evaluation results show that the uninhabitable housing program has been running in accordance with applicable policies and has achieved development targets each year, so that many people are helped because they can have decent housing to improve the standard of living and health of the recipient community.